Program Kegiatan Taman Baca Masyarakat (TBM) Ridha Di Kelurahan Teladan Kota Kisaran Kabupaten Asahan untuk Menarik Perhatian Masyarakat - Nur’aini, Nur’aini; Lubis, Misdahwati; Azzahra, Dita (Universitas Negeri Padang, 2023)
This study aims to find out the program of activities at the Ridha Community Reading Center (TBM) and ways to educate the Asahan community by making people like reading and improving the quality of reading interest in Teladan Village, Kisaran Regency. The method used in this research is qualitative research with a descriptive approach. Data collection techniques were carried out by means of observation, interviews and documentation. In the data analysis section using data reduction, data presentation and drawing conclusions. The validity of the data in this study used source triangulation, time triangulation, and method triangulation. The results of this study indicate that the Ridha Community Reading Center (TBM) activity program in the exemplary urban village of the Asahan district can attract the public's attention by creating various programs, while the activity programs provided by Ridha's TBM to attract the public's attention are: 1). reading corner; 2). library cart; 3). reading taxis and smart stalls; 4). Declaration of literacy village; 5). Workshops; 6). Storytelling; 7). Dancing the Gubang dance; 8). white swallow martial arts; 9). Poetry reading and poetry reading competitions; 10). Traditional game practice; 11). Social inclusion (learning to make savory banana chips and roll cakes); 12). Aerobic Gymnastics and 13). TBM Ridha Studio. An activity program that makes the Asahan community gain knowledge and very useful learning.